Grafting polyzwitterions onto polyamide by click chemistry and nucleophilic substitution on nitrogen: A novel approach to enhance membrane fouling resistance - Yu, Hai-Yin; Kang, Yan; Liu, Yaolin; Mi, Baoxia (Journal of membrane science, 2014)
We present a first-of-its-kind use of click chemistry to graft polyzwitterions (PZs) onto polyamide, the most widely used material to make semi-permeable membranes for desalination and water purification. We have also experimentally proven that SN2 nucleophilic substitution on nitrogen can occur on the polyamide polymer chain under mild reaction conditions, as opposed to harsh reaction conditions required by many traditional grafting approaches. To prepare the click reaction, we synthesized an alkyne-PZ via reversible addition-fragmentation chain-transfer radical polymerization, followed by functionalizing polyamide with azide functional groups through bromination and subsequently SN2 nucleophilic substitution of Br with azide. The alkyne-PZ was then grafted to azide-polyamide by an azide–alkyne cycloaddition click reaction. The PZ-grafted polyamide became much more hydrophilic than the virgin polyamide. Results of Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy indicated that a successful click reaction and almost full surface coverage by PZ were achieved under studied experimental conditions. Membrane flux testing in a forward osmosis mode showed that the PZ grafting did not significantly affect the water flux of a polyamide membrane, thereby demonstrating the new grafting approach as a safe route for the surface modification of polyamide membranes. Besides, the PZ-grafted polyamide membrane exhibited excellent antifouling capability, which can be attributed to the shielding of specific binding sites on membrane surface, strong hydrophilic repulsion caused by local charge-induced hydration forces, and steric repulsion introduced by the brush-like flexible PZ chains. Therefore, this study opens a new avenue to surface modification of polyamide with different functional polymers and hence paves the way to a next generation of high-performance polyamide membranes. [Display omitted] •First-of-its-kind use of click chemistry to graft polyzwitterions onto polyamide.•Nucleophilic substitution on nitrogen can occur on the amide group.•It opens a new avenue to surface modification of polyamide membrane.•Polyzwitterion grafting results in excellent antifouling performance.